Fabrication of nanofiltration hollow-fiber membrane for the separation of xylose-glucose - Siti Normunira, Ramli (2014)
Biomass is a biological material derived from living things, or recently living organism. Abundant plant biomass has the potential to become a renewable energy source of fuels and chemicals. Monosaccharide produced from the fermentation of biomass could produce various types of biofuels such as ethanol, butanol, methane, biodiesel, and hydrogen which greatly useful as sustainable energy. By the hydrolysis process of biomass, glucose and xylose were the most hemicelluloses sugar found in biomass. Nanofiltration membranes could offer a relatively cost-competitive separation steps, less complex and easier to maintain compared to chromatographic methods. The objective of this study is to produce PES hollow fiber nanofiltration membrane for the separation of xylose and glucose. Polyethersulfone (PES) polymer was used in a spinning solution with polyvinylpyrrolidone (PVP) as an additive to the solution. The performances of the membrane were investigated by varying the concentration of PVP from 1 wt. %, 3 wt. %, 7 wt. % and 9 wt. %. The surface morphological structure of the NF membrane were clarifying using SEM test. The performances test of membrane was carried out by separated a xylose and glucose. HPLC separation test was used to analyse the samples from the separation process. The result from this experiment is the composition of xylose in permeate is larger than glucose since xylose has lower molecular size than glucose. The results showed that, as the concentration of additive increase, the fluxes also increase and the sugar rejection will lower. As the concentration of PVP increase, the separation of xylose and glucose increase based on the xylose separation factor and solute rejection of xylose and glucose in the mixture solution.